LATE PRESENTATION OF ADVANCED CENTRAL PRECOCIOUS PUBERTY - Bahrudin, Mohd Fyzal; Jayaraman, Parvina; Abdullah, Noor Rafhati Adyani (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Precocious puberty is characterized by the emergence of secondary sexual traits in females before the age of eight, and in males before the age of nine. Late presentation in a setting of precocious puberty inadvertently resulted in short final adult height. We describe a case of advanced central precocious puberty diagnosed at a later stage. CASE A 9-year-old female visited Klinik Kesihatan with symptomatic anaemia. Later, at 10 years and 4 months old, she visited the combined reproductive endocrine clinic. Her mother was unsure of her exact height changes, but she weighed 42 kg (>97th centile) and experienced thelarche at 6-7 years old. She attained pubarche at 8 years old and menarche at 8 years and 6 months old. Her bone age was advanced >3.4 SD with an estimated bone age of 14 years and a chronological age of 10 years and 8 months. Her height was 147 cm (3rd centile). Hormonal profiles revealed E2 82 pg/mL, LH 10.34 IU/L, FSH 4.7 IU/L, Prolactin 573.7 m IU/L, TSH 1.08 m IU/L (0.35-4.94), T4 11.83 pmol/L (9-19.05), DHEAS 3.2 ug/dL (0.92-7.6), Basal 17-OHP 12.64 nmol/L (1.2-11.4). Synacthen 17-OHP test ruled out nonclassical congenital adrenal hyperplasia with peak 17-OHP 21.8 nmol/L at 60 minutes. Transabdominal sonography revealed a uterus 5.8 cm x 3.8 cm with an endometrial thickness 11.55 mm. No obvious ovarian/adnexal mass and no obvious adrenal mass. Elevated LH level >0.3 IU/L indicates central precocious puberty and obviates the need for further GnRH stimulation test. IM Decapepty (Triptorelin) 3.75 mg monthly was administered to arrest her puberty aiming to reduce psychosocial stress due to early menarche and to improve final adult height. CONCLUSION Menarche is a late manifestation of puberty. In cases where a young girl presents with menses, likely, the optimal timing for pubertal blocker administration has already been missed. Therefore, early detection and management of precocious puberty is imperative.